The Effectiveness of Tic Tac Toe Game in Enhancing Arabic Vocabulary of Fifth Grade Students at MIN 1 Kota Banda Aceh - Abdullah, Abdullah; Badruzzaman, Badruzzaman; Fakhrul Ramadhan, Noval (لســـانـنــا (LISANUNA): Jurnal Ilmu Bahasa Arab dan Pembelajarannya, 2025)
The students of MIN 1 Kota Banda Aceh often face difficulties in understanding Arabic vocabulary due to the limited use of effective teaching methods, which leads to low motivation and boredom in learning. This study aims to examine the effectiveness of using the Tic Tac Toe game as a teaching aid to improve students’ Arabic vocabulary and to identify their responses to this method. A quasi-experimental design was employed, involving both experimental and control groups, with pre-tests, post-tests, and a questionnaire as data collection tools. The findings indicate that Tic Tac Toe is effective in enhancing students’ vocabulary mastery, as shown by the independent t-test results using IBM SPSS Statistics 22 with a significance value of 0.01 < 0.05, confirming the acceptance of the alternative hypothesis. Furthermore, the students’ responses were highly positive, with 97% indicating favorable attitudes toward the use of Tic Tac Toe in learning Arabic vocabulary.